The more accurate determination of surface excitation parameters, the more accurate quantitative surface analysis. (November 2022) - Hajati, S.; Dashtian, K.; Moradi, M.; Toth, J.; Keyhan, M.
Abstract: The accurate quantitative surface analysis for the study of nanostructures practically used for e.g. photocatalysis, electrocatalysis, energy storage and sensing applications is of high importance. Moreover, the accurate quantitative electron spectroscopy and analytical microscopy of semiconducting nanomaterials such as nano-photocatalysts relies on the accurate determination of surface excitation parameters (SEP). Reflection electron energy loss spectroscopy (REELS) as a surface sensitive technique could be applied for the determination of SEP. The chemical, mechanical, thermal stability, optical and dielectric properties of Ni6 MnO8 as binary metal oxide makes such structure suitable for practical applications. Therefore, here Ni6 MnO8 due to its great importance in its special applications was typically studied by REELS using the Yubero-Tougaard algorithm, which is based on dielectric response theory. After an extrapolation process applied to the obtained REELS spectrum, the energy gap (Eg) of this material was obtained to be 3 eV. The surface and bulk energy loss functions of the material were also determined. The values of inelastic mean free path (IMFP) of the electrons of different energies in the range of 500–4000 electron volts travelled in Ni6 MnO8 were determined. In addition, from the obtained energy loss function (ELF), by using the Kramers-Kronig transformations of the real and imaginary parts of dielectric function (ε), the important optical parameters of Ni6 MnO8 such as refractive index (n), attenuation coefficient (k) and absorption coefficient (μ) were determined. Finally, as a critical parameter in quantitative electron spectroscopy, the SEP and its angular distribution were determined. It was found that the Pauli-Tougaard model requires a modification to make it better descriptive to well fit the SEP data for a given material. Therefore, a more accurate model was obtained to make a better surface analysis and analytical microscopy. Highlights: Application of Reflection electron energy loss spectroscopy. Determination of surface excitation parameters (SEP). Development of a model to accurately describe SEP and its angular distribution. Making the possibility of more accurate quantitative electron spectroscopy. Making the possibility of more accurate quantitative analytical microscopy.